Communication strategies in an international school citizen science program investigating marine litter - Thiel, Martin; Baeza Álvarez, Jostein; Diaz, Manuel; de Veer, Diamela; Dittmann, Sinja; Guevara-Torrejón, Valeska; Ahumada, Geraldine Holtmann; Honorato-Zimmer, Daniela; Kiessling, Tim; Leyton Muñoz, Ailin; López-Xalín, Ninoshka; Nuñez, Paloma; et al. (Frontiers in Environmental Science, 2023)
Communication is an essential element of science, and while it is important in all scientific endeavors, it gains substantial strategic relevance in citizen science projects. For a school citizen science program to be successful, an adequate communication strategy needs to achieve a balance between learning objectives and the generation of scientific knowledge. In this community case study, we report on the communication strategies of an international network, namely the citizen science program "Científicos de la Basura" (Litter Scientists), which collaborates with schoolteachers and schoolchildren to investigate anthropogenic litter on marine beaches and in rivers. The program has been active in Chile since 2007, and as of 2018, it had expanded to the 11 countries from the central and southern East Pacific. More than 40 teachers and collaborators from these countries work in this network making an effort to connect the research activities with the learning objectives of the school curriculum. The communication between the coordination team and the teachers includes three main elements (1 -design and planning; 2 -training and research; 3 -evaluation and sharing), with the following activities: (1a) regular internal communication within the coordination team to design, motivate and supervise adequate research projects, (1b) communication with teachers to design appropriate learning materials (co-creation) and get their feedback on the planned research activities, (2a) sharing the final research plan and transfer methodological skills through regular training of the teachers, (2b) responding to methodological questions by the teachers about the sampling, and coordinate data collection and validation, (3a) guiding teachers and schoolchildren in the evaluation and interpretation of their research results, and (3b) encouraging teachers and schoolchildren to communicate their scientific findings to the wider community. Intense internal communication and regular exchange with teachers guarantees 3 successful learning and rigorous scientific information. The main challenges for the program are team capacity, socio-economic stability, internet access, and teachers' workloads. Recommendations to achieve successful communication and good science are efficient team communication skills, customized contacts, collaborative work, guidance of field work, feedback from participants, and promoting the sense of community.